THE REMAINING CHEMICAL COMPOUNDS OF THE BODY'S METABOLISM ARE REDUCED THROUGH THE HEMODIALYSIS METHOD - Susanto, Vetra; Dewi AS, Mutia; Suryani, Suryani; Suriani, Endang; Dasa Wardhani, Sri Muri (LLDIKTI X Sumbar, Riau, Jambi, Kepri, 2025)
The accumulation of metabolic residual chemical compounds, such as urea, and creatinine, is a major consequence of decreased glomerular filtration function in patients with chronic kidney disease (CKD). Increased concentrations of these compounds trigger internal homeostasis disorders and accelerate the progression of metabolic complications. Hemodialysis is a kidney replacement therapy that aims to eliminate toxic compounds and maintain the body's biochemical balance. The purpose of this study is to evaluate the effectiveness of hemodialysis in reducing urea, creatinine, and uric acid levels in CKD patients. The pre-post test research involved 30 stage V CKD patients who underwent routine hemodialysis at the Regional General Hospital (RSUD) Padang Panjang, West Sumatra. Venous blood samples were taken 15 minutes before and after a single hemodialysis session. Urea levels were analyzed using the urease-GLDH method, creatinine using the kinetic Jaffé method, and uric acid using the uricase-POD method. The data were analyzed using a paired t-test with a significance level of p<0.05.The results were obtained The average urea level decreased from 182.6 ± 28.7 mg/dL it was concluded that Hemodialysis significantly reduced the level of chemical compounds left over from the body's metabolism in patients to 76.3 ± 16.9 mg/dL (p<0.001), creatinine from 11.8 ± 2.9 mg/dL to 4.9 ± 1.3 mg/dL (p<0.001), and uric acid from 8.5 ± 1.8 mg/dL to 5.2 ± 1.1 mg/dL (p<0.001). It can be concluded that hemodialysis significantly reduces the level of chemical compounds left over from the body's metabolism in advanced CKD patients. Hemodialysis maintains biochemical homeostasis and reduces the risk of systemic complications.